2016
DOI: 10.3390/molecules21020233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Treatment Conditions on the Properties of Dental Silicate Cements

Abstract: Abstract:In this study the sol-gel process was used to synthesize a precursor mixture for the preparation of silicate cement, also called mineral trioxide aggregate (MTA) cement. This mixture was thermally treated under two different conditions (1400˝C/2 h and 1450˝C/3 h) followed by rapid cooling in air. The resulted material (clinker) was ground for one hour in a laboratory planetary mill (v = 150 rot/min), in order to obtain the MTA cements. The setting time and mechanical properties, in vitro induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…A previous study showed that hydrated calcium silicates (calciumsilicate-hydrate, CSH) have needle-like and plate microcrystal morphologies and spongy agglomeration of carbonate phases. 25 In this study, the microstructure of 100C 3 S appeared to be more compact than that of the 100C 2 S sample. In the early stage of hydration, the newly formed CSH crystals were acicular or spongy shaped.…”
Section: Resultsmentioning
confidence: 51%
“…A previous study showed that hydrated calcium silicates (calciumsilicate-hydrate, CSH) have needle-like and plate microcrystal morphologies and spongy agglomeration of carbonate phases. 25 In this study, the microstructure of 100C 3 S appeared to be more compact than that of the 100C 2 S sample. In the early stage of hydration, the newly formed CSH crystals were acicular or spongy shaped.…”
Section: Resultsmentioning
confidence: 51%
“…In addition, SEM images showed uniform distribution of these phases in the polymeric matrix and EDX spectrum demonstrated the presence of barium and strontium as radiopacifying elements. The diffractogram performed on BIO MTA+ anhydrous powder indicated the presence of calcium silicates as major phases—Ca 3 SiO 5 , Ca 2 SiO 4 , and Bi 2 O 3 [7,8,27,28,29]. The addition of Bi 2 O 3 is required, radiopacity being one of the basic requirements of a dental material [30], observing that hydro compounds resulting from the setting reaction are deposited on its surface.…”
Section: Discussionmentioning
confidence: 99%
“…MTA is a hydraulic cement, and a tricalcium silicate-based material. The MTA composition has predominantly Portland type I cement, which has the main crystalline solid phases: alite (tricalcium silicate, 3CaO·SiO 2 , C 3 S), belite (dicalcium silicate, 2CaO·SiO 2 , C 2 S), cellite (tetracalcium aluminoferrite, 4CaO·Al 2 O 3 ·Fe 2 O 3 , C 4 AF) and tricalcium alluminate (3CaO·Al 2 O 3 , C 3 A), with the following main oxide components: CaO, SiO 2 , Al 2 O 3 , and Fe 2 O 3 [6,7,8]. Besides this, in the MTA’s composition there are Ba and Sr oxides with opacifying roles [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported in the literature showed that the biological properties of the sol-gel materials were affected by the heat treatment carried out after the gel formation [ 31 , 32 , 33 , 34 , 35 ]. When the transition from sol to gel occurs, indeed, both hydrolysis and condensation reactions are incomplete and, thus, reactive silanols are still present in the system.…”
Section: Introductionmentioning
confidence: 99%